PENGARUH CITRA MEREK DAN HARGA TERHADAP NIAT BELI PRODUK PADA SUPERMARKET SYARIAH DENGAN MODERASI RELIGIUSITAS - Dwi Nina Agustin, Diana; Sutarso, Yudi (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research was conducted with the aim of knowing the influence of brand image and price on product purchase intentions at 212 Mart with moderate religiosity. The research method used is a quantitative method with a non-probability sampling technique with a purposive sampling method to determine the research sample. This study involved consumers or customers at 212 Mart with a sample size of 130 respondents. Data analysis was carried out with WarpPLS. The results of this research show that 1) brand image has a positive effect on purchase intention; 2) price has a positive effect on purchase intention; 3) the moderating role of religiosity is not confirmed on the influence of brand image on purchase intention; 4) the moderating role of religiosity is not confirmed in terms of the influence of price on purchase intention. For practitioners, this study provides guidance on how to manage brand image and price to increase purchase intentions.